2015
DOI: 10.1111/jre.12326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of full‐mouth disinfection and quadrant‐wise scaling in the treatment of adult chronic periodontitis: a systematic review and meta‐analysis

Abstract: Scaling and root planing are widely considered as effective methods for treating chronic periodontitis. A meta-analysis published in 2008 showed no statistically significant differences between full-mouth disinfection (FMD) or full-mouth scaling and root planing (FMS) and quadrant scaling and root planing (Q-SRP). The FMD approach only resulted in modest additional improvements in several indices. Whether differences exist between these two approaches requires further validation. Accordingly, a study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 42 publications
3
32
0
1
Order By: Relevance
“…The addition of FMD to FM-SRP or quadrant SRP (Q-SRP) is effective (13,14) and does not cause any obvious discomfort or change in one's quality of life (15). Moreover, based on a recent meta-analysis, FMD, FMS, and Q-SRP all effectively manage CP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of FMD to FM-SRP or quadrant SRP (Q-SRP) is effective (13,14) and does not cause any obvious discomfort or change in one's quality of life (15). Moreover, based on a recent meta-analysis, FMD, FMS, and Q-SRP all effectively manage CP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, based on a recent meta-analysis, FMD, FMS, and Q-SRP all effectively manage CP. Comparison of FMD and Q-SRP revealed that FMD was moderately better than Q-SRP in reducing probing depth and increasing clinical attachment level (13). Therefore, we used FMD and FM-SRP as the treatment of choice to restrict the cumulative effect of bacteremia and avoid repeated acute inflammation during treatment (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these reviews indicate a small additional clinical benefit of these drugs as compared to scaling and root planing alone (Fritoli et al., ; Herrera, Alonso, León, Roldán, & Sanz, ; Jepsen & Jepsen, ; Keestra, Grosjean, Coucke, Quirynen, & Teughels, ; Kolakovic, Held, Schmidlin, & Sahrmann, ; Santos et al., ; Sgolastra, Severino, Petrucci, Gatto, & Monaco, ; Slots & Ting, ; Smiley et al., ; Zandbergen, Slot, Niederman, & Van der Weijden, ). Regarding the question of the relative benefit of one‐day full‐mouth disinfection (FDIS) approach over the traditional quadrant‐based scaling and root planing (qSRP) approach, only a few systematic reviews exist (Eberhard, Jepsen, Jervøe‐Storm, Needleman, & Worthington, , ; Fang et al., ; Farman & Joshi, ; Lang, Tan, Krähenemann, & Zwalen, ). These conclude that there is no clear evidence for a benefit of FDIS over qSRP.…”
Section: Introductionmentioning
confidence: 99%
“…Such procedure often required intravenous sedation, which was performed by the physician in charge. This particular procedure requires the dental surgeon to be prepared for the possible clinical needs of the patients, as well as to always respect their individuality and urgent needs in order to solve the oral issues that may and are affecting the systemic health of critically ill patients [48,49].…”
Section: Dentistry Interventions In An Intensive Care Unitmentioning
confidence: 99%